Potential‐Modulated Ion Distributions in the Back‐to‐Back Electrical Double Layers at a Polarised Liquid|Liquid Interface Regulate the Kinetics of Interfacial Electron Transfer. Issue 3 (27th December 2022) - Gamero‐Quijano, Alonso; Manzanares, José A.; Ghazvini, Seyed M. B. H.; Low, Paul J.; Scanlon, Micheál D.
Abstract: Biphasic interfacial electron transfer (IET) reactions at polarisable liquid|liquid (L|L) interfaces underpin new approaches to electrosynthesis, redox electrocatalysis, bioelectrochemistry and artificial photosynthesis. Herein, using cyclic and alternating current voltammetry, we demonstrate that under certain experimental conditions, the biphasic 2‐electron O2 reduction reaction can proceed by single‐step IET between a reductant in the organic phase, decamethylferrocene, and interfacial protons in the presence of O2 . Using this biphasic system, we demonstrate that the applied interfacial Galvani potential difference Δ o w φ Δ _o^wφ provides no direct driving force to realise a thermodynamically uphill biphasic IET reaction in the mixed solvent region. We show that the onset potential for a biphasic single‐step IET reaction does not correlate with the thermodynamically predicted standard Galvani IET potential and is instead closely correlated with the potential of zero charge at a polarised L|L interface. We outline that the applied Δ o w φ Δ _o^wφ required to modulate the interfacial ion distributions, and thus kinetics of IET, must be optimised to ensure that the aqueous and organic redox species are present in substantial concentrations at the L|L interface simultaneously in order to react. Abstract : Biphasic interfacial electron transfer : Using the biphasic 2‐electron O2 reduction reaction at a polarised liquid|liquid interface, the applied interfacial Galvani potential difference is shown to provide no direct driving force to realise a thermodynamically uphill interfacial electron transfer (IET) reaction. Thermodynamically spontaneous IET is kinetically inhibited until is tuned to modulate the ion distributions such that all species involved in the biphasic reaction are present at the interface in significant concentrations simultaneously.